Determinants of Banking Profitability: The Case of State-Owned Banks Listed on the Indonesia Stock Exchange - Imam Muhtadin; Faris Rahman Zain; Edi Purwanto; Tiyas Puji Utami (Journal of Accounting and Investment, 2022)
Research aims: This study examined the determinants of profitability of state-owned banking companies on the Indonesia Stock Exchange, including Adequacy Ratio (CAR), Operating Costs and Operating Income (OCOI), Loan to Deposit Ratio (LDR), and Non-Performing Loan (NPL).Design/Methodology/Approach: This study is quantitative research with a type of exploratory. The population in this study was all state-owned banks listed on the Indonesia Stock Exchange for the period 2012-2018 and used the saturated sample technique, or the entire population was taken as a sample. The data analysis method employed in this study was a panel data regression model (a combination of time series and cross section) utilizing the EViews 9.Research findings: The results in this study revealed that the CAR and OCOI had a negative effect on bank profitability as proxied by ROA. Meanwhile, LDR and NPL did not affect the profitability of state-owned banks.Theoretical contribution/Originality: The research contributes to the literature and practice. Practically, these results can be used for management to maintain the banking system's internal condition in pursuing profitability.